Kualitas dan Karakteristik Hadis-Hadis Bayan Tafsir Al Quran dalam Fikih Kewarisan - Maizuddin Maizuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Abstract: One of the functions of hadith is the bayan (explanation) of interpretation, i.e. to clarify, specify, restrict or expand what is mentioned in the Qur'an. In order to be the bayan of interpretation, hadith must meet material truth as the story that comes from the Prophet and its righteousness in term of its dilalah (signs). The conclusions of jurisprudence laws have been produced based on the bayan function of hadith interpretation, including in the field of inheritance. However, there are some criticisms of these hadith, both in terms of their material truth, or their use as the bayan of interpretation. Based on these problems, this study focused on answering two main questions; regarding the quality of hadith as the bayan of interpretation in the jurisprudence of inheritance and the characteristics of the hadith as the bayan of interpretation in the inheritance jurisprudence. The study results showed that one of the five hadith is hadith dha'if in the category of munkar, another one is hadith hasan, and the other three are hadith sahih. Regarding the characteristics of the hadith as bayan of interpretation, it can be explained that jurisprudence laws use hadith dha'if, rawi gharib in some thabaqat, hadith that came early to interpret the verses of Quran coming later, and the full power of the hadith fi'li to deflect the sharih meaning of the Quran.Abstrak: Salah satu fungsi hadis adalah bayan tafsir, yaitu memperjelas, merinci, membatasi atau memperluas apa yang disebutkan dalam al-Qur'an. Untuk dapat menjadi bayan tafsir tersebut, hadis harus memenuhi syarat kebenaran materil sebagai riwayat yang datang dari Nabi dan kebenaran-Nya dari dilalahnya. Kesimpulan hukum fikih telah banyak dihasilkan berdasarkan fungsi bayan tafsir hadis, termasuk di bidang kewarisan. Tetapi ada beberapa kritik terhadap hadis-hadis ini, baik dari segi kebenaran materi, atau penggunaannya sebagai bayan tafsir. Berdasarkan hal ini, penelitian difokuskan untuk menjawab dua pertanyaan utama: menyangkut kualitas hadis bayan tafsir dalam fikih kewarisan, dan berkenaan karakteristik hadis bayan tafsir bayan dalam fikih warisan. Dari hasil penelitian, salah satu dari lima hadis tesebut termasuk hadis dha'if dalam kategori munkar, sementara satu hadis berstatus hasan, dan tiga hadis lagi berstatus sahih. Mengenai karakteristik hadis-hadis bayan tafsir, dapat dijelaskan bahwa terdapatnya penggunaan hadis dha’if, rawi-rawi yang gharib dalam beberapa thabaqat, penggunaan hadis yang turun lebih awal untuk menafsirkan ayat-ayat Alquran yang turun kemudian, dan kekuatan penuh hadits fi'li untuk membelokkan makna sharih dari Alquran.